Band gap engineering through calcium addition in (Mg, Co, Ni, Cu, Zn)O high entropy oxide for efficient photocatalysis - Gautam A.; Das S.; Ahmad M.I. (My University, 2025)
Multicomponent metal oxides have shown the potential to be excellent catalysts mainly because of synergistic interactions between the active sites. We report (Co, Mg, Ni, Cu, Zn)1-xCaxO (x = 0.05, 0.1) high entropy oxide (HEO) photocatalyst with single phase rocksalt structure (space group Fm3¯m) synthesized by solution combustion synthesis (SCS) technique. HEOs contain elements with varying electronegativities and crystal field splitting and thus exhibit a relatively lower band gap when compared to the individual constituent oxides. Adding Ca2+ results in increased covalency due to the greater exchange interaction between O 2p and transition metal (TM) 3d orbital, engendering further reduction in band gap and consequently improving photocatalytic activity in the visible region. In addition, the introduction of point defects, mainly metal/oxygen vacancy, to accommodate the larger size Ca2+ cation also contributed to the catalytic activity. The photocatalytic activity enhancement is demonstrated by visible light-assisted photodegradation of methylene blue (MB). The MB dye degradation rate constant for (Co, Ni, Cu, Zn, Mg)0.9Ca0.1O catalyst was found to be ∼0.0445 min−1, which was about six times faster than that of the pristine (Co, Mg, Ni, Cu, Zn)O. © 2024